’’تلفیق بین المذاہب ‘‘فقہ اسلامی کے تناظر میں : Application of Talfeeq in Different School of Thoughts in perspective of Islamic Fiqh - Muhammad; Muhammad, DR,Sahibzada Baz (Journal of Quranic and Social Studies, 2021)
The spirit of religion is Tawheed and the Prophet (peace and blessings of Allaah be upon him), and it is a new and coverlid phrase, to juxtapose in one issue or various issues,and to adopt various jurists, points of view is called “talfeeq” in the present redical age of science and technology every social faculty is being radicalized particularly to follow to one Imam, there are different point views about “taqleed” and “talfeeq”. Some Scholars are thought that there are No permission of “talfeeq” in Islamic Fiqh because it is obeying of Nafs and it make a major fault in religion, Other Scholars think that “ talfeeq “ Should be allowed because it’s based on “usar” easiness of deen . In this article I take a research Analysis about this Issue and make a balance opinion about “taqleeq” and “talfeeq”.